Sensitivitas dan Spesifisitas Rasio Lingkar Pinggang Panggul (RLPP) dan Lingkar Perut (LP) sebagai Indikator Risiko Hipertensi pada Orang Dewasa: Sensitivity and Specificity of the Ratio of Waist-Pelvic Circumference (RLPP) and Abdominal Circumference (LP) as an Indicator of Hypertension Risk in Adults - Ahdiyatul Fauza; Ali Rosidi (Fakultas Keperawatan Universitas Andalas, 2017)
Obesity is a risk factor for increased blood pressure and triglyceride levels, which then becomes a risk factor for cardiovascular disease. Measuring waist circumference ratio to know the high risk of DM II disease, cholesterol, hypertension, and heart. Measurement of abdominal circumference is done to determine whether there is abdominal or central obesity. This type of obesity is very influential on the incidence of disease complications. This research is a cross-sectional analytic research. Subjects of adults aged 30-60 years are from secondary data of metabolic syndrome study which has been examined for blood pressure and stomach circumference of 45 people in Laboratory of West Sumatera. The sensitivity and specificity tests were performed using Receiver Operator Characteristic Curve (ROC). Age of respondents in general in the range 50-60 years with a percentage of 64.4%. Based on the ROC curve, RLPP has the ability to identify the standard hypertension indicator (AUC 0.783) is not good enough as an indicator to detect the risk of complications in hypertension and poor (poor AUC 0.648) as an indicator of hypertension risk. The ROC results show that RLPP is slightly better than LP but both are not reliable enough as indicators for hypertension.